Cancer Patients' Recommendations for Nature-Based Design and Engagement in Oncology Contexts: Qualitative Research. (April 2018) - Blaschke, Sarah; O'Callaghan, Clare C.; Schofield, Penelope
Objectives: To explore cancer patients' recommendations for nature engagement based on their subjective nature experiences and observations in the cancer setting. The rationale was to gain practical insight for delineating relevant and translatable nature-based care and design opportunities in oncology contexts. Background: Innovative cancer care services are needed to respond to growing demand and shifting healthcare needs. Engagement with nature has shown multiple health benefits and presents a promising opportunity for application in healthcare to improve outcomes. Method: Qualitative research design using content analysis was used. Eligible adults with any cancer diagnosis participated in semistructured and audio-recorded interviews. Transcribed textual data included responses to two open-ended questions querying about participants' recommendations related to nature-based opportunities in the cancer setting. Deductive analysis used three predetermined categories: "recommendation: features, " "recommendation: functions, " and "cautions." Results: Twenty patients with cancer (nine female) participated. Broad recommendations incorporated (1) using nature for vital sensory stimulation and engagement, (2) using nature for personal space and freedom to enable private and social exploration, (3) using views to nature for distraction and comfort, and (4) accessing nature for physical activity and movement. Three critical factors were determined for avoiding adverse experiences: determining appropriate expenditure and resourcing, selection of appropriate nature-based design materials, and exercising caution around demanding nature engagement and harsh weather conditions. Conclusions: Cancer patients' recommendations reveal the importance of engaging with nature in their experiences of health and recovery. The findings can inform planning appropriate and safe integration of beneficial nature engagement in cancer settings and support services.